The real crisis of the church - Dreyer, Wim A. (HTS teologiese studies, 2015)
What is the real crisis of the church? Very often, clergy, churches and congregations experience a ‘crisis’ only when membership is in decline, resulting in financial hardship. Crisis is limited to stress which the church as institution experiences when structures, finance and traditions are under pressure. In this contribution, the point is argued that the real crisis of the church is not to be found in institutional challenges, but in the inability of the church to be what it already is. With reference to Karl Barth’s ecclesiology, this contribution departs from the assumption that the real crisis of the church is not only to be found in external circumstances and influences, but is primarily a question of the church not being able to ‘be church’. Continued reformation of the church is of utmost importance.